2007
DOI: 10.1302/0301-620x.89b7.18751
|View full text |Cite
|
Sign up to set email alerts
|

The value of MRI undertaken immediately after reduction of the hip as a predictor of long-term acetabular dysplasia

Abstract: Our aim was to determine whether abnormalities noted on MRI immediately after reduction for developmental dysplasia of the hip could predict the persistance of dysplasia and aid surgical planning. Scans of 13 hips in which acetabular dysplasia had resolved by the age of four years were compared with those of five which had required pelvic osteotomy for persisting dysplasia. The scans were analysed by two consultant musculoskeletal radiologists who were blinded to the outcome in each child. The postreduction sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 11 publications
0
19
1
Order By: Relevance
“…Mitchell et al (17) compared the MRI images of 13 patients showing successful early reduction with 4 cases of failed reduction who ultimately needed pelvic osteotomy. They determined the value of MRI immediately after reduction of the hip as a predictor of long-term acetabular dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell et al (17) compared the MRI images of 13 patients showing successful early reduction with 4 cases of failed reduction who ultimately needed pelvic osteotomy. They determined the value of MRI immediately after reduction of the hip as a predictor of long-term acetabular dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell described the value of MRI undertaken immediately after reduction to minimize the need of sedations [13]. Conroy et al [9] found that STIR (Short TI Inversion Recovery) or TIRM (Turbo-Inversion Recovery-Magnitude) imaging in axial planes provided adequate information regarding the position of the femoral head relative to the acetabulum.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is a superior soft-tissue contrast resolution which allows differentiation between articular structures such as bone, hyaline and fibrous cartilage, ligaments, joint capsule, intra-articular tissues and fluids [14][15][16]. The appearance of the paediatric hip has been widely documented in control patients and in DDH cases [9][10][11][12][13][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%